A Call for Corporate Leadership to Sustain And Reinvigorate a Culture of Arbitration. Issue 3 (21st February 2018) - Burt, David H.
Abstract : Business‐to‐business dispute arbitration—once the customized, streamlined, speedy and confidential route to solving disputes—has now long lost those charms. Many business customers believe they are poorly served by its present state.